Pandangan Hukum Keluarga Islam terhadap Manajemen Konflik Ekonomi Dalam Rumah Tangga: Views of Islamic Family Law on Economic Conflict Management in the Household - Permasari, Rama Dhini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This paper discusses about Islamic Family Law View on Economic Conflict Management in the Household. This research is motivated by the findings of many previous research results regarding the high divorce rate, the main cause of which is due to economic problems in the household. It is important to study how Islamic Family Law provides solutionsto economic problems that occur between husband and wife so that divorce can be avoided. His research is included in the type of library research (library research). To process the data that the author has obtained. So the authors analysis using content analysis techniques (content analysis). The results of this research is incuded in the type of library research. To process the data that the authors analyza using content analysis techniques. The result of this study reveal that the solutions for resolving economic conflict in the household in the view of islamic Famiy Law include: the husband fulfills the rights of his wife, the wife must know when she has the right to earn a living from her husband, the wife must know when she has the right to earn a livingfrom her husband, the wife must not demand rights beyond the limits of the husband’s ability, the wife must be patient and sincere with her husband.